PENGEMBANGAN MEDIA PANCA (PADEPOKAN PANCASILA) PADA MATERI SILA-SILA PANCASILA KELAS II SEKOLAH DASAR - Oktavia Wahyu Saputri (Universitas Muhammadiyah Gresik, 2022)
Interviews with second grade teacher there are several problem including the use of learning media that is limited to pictures, student textbooks and caterpillar media that exits in ganeral. This study aims to develop Panca learning media in civics subjects the material of the Pancasila precepts for second grade at UPT SD Negeri 24 Gresik for the 2020/2021 Academic Year. The process of developing lesrning medi using the ADDIE development model which consist of 5 stages, namely : Analysis, Design, Development, Implementation and Evaluation. The subjects in this study consisted of six students of second grade at UPT SD Negeri 24 Gresik. Data collection techniques and instruments used in the study were interviews, validator sheets and questionnaire respon from second grade students. The Panca Learning for the precepts of pancasila have gone through saveral stages of expert validation and student responses show that the Panca learning media meets goode criteria. These criteria include the validation of learning media carried out by 2 validators ( elementary school education lecturers) obtaining and avarage value of 86% so that ist is categoraed as “feasible”, and material validation carried out by 2 validators ( UPT SD Negeri 24 Gresik teachers) obtaining an avarage of 92,5% so that catagorized as “very fasible” and the response of students who scored 92,5% so that this Panca Learning media is effectively used in the learing of second grade students.